OsGIF1 Positively Regulates the Sizes of Stems, Leaves, and Grains in Rice - He, Zhongshan; Zeng, Jing; Ren, Yun; Chen, Dan; Li, Wenjie; Gao, Fengyan; Cao, Ye; Luo, Tao; Yuan, Guoqiang; Wu, Xianghong; Liang, Yueyang; Deng, Qiming; et al. (Frontiers in Plant Science, 2017)
GRF interacting factors (GIFs) are involved in several developmental processes in Arabidopsis. We previously showed that upregulation of OsGIF1 expression improves rice grain size. However, whether OsGIF1 is involved in other developmental processes remains unclear. Here, we report pleiotropic effects of OsGIF1 on rice organ size regulation. Overexpression and functional knock-out via a CRISPR/Cas9 strategy revealed that OsGIF1 not only positively regulates the sizes of rice leaf, stem, and grain but also influences rice reproduction. Expression profiles based on both qRT-PCR and GUS (β-glucuronidase) histochemical staining suggested that OsGIF1 is differentially expressed across various rice tissues, consistent with its roles in regulating the development of multiple rice organs. Additionally, we found that OsGIF1-YFP localized preferentially in the nucleus, which supports its proposed role as a transcriptional cofactor. Further histological analysis suggested that OsGIF1 affected rice organ size possibly by regulating cell size. Our results suggest that OsGIF1 plays important roles in vegetative and reproductive developmental processes, with important implications for rice breeding.